2018
DOI: 10.1111/medu.13548
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clerkship on students’ stigma towards mental illness: a meta-analysis

Abstract: The robust effect of clerkship on students' stigma of mental illness established by the present meta-analysis highlights its role as a crucial curriculum component for experiential learning and as a necessary agent for the battle against stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 54 publications
1
36
0
1
Order By: Relevance
“…By virtue of the same tendency, high-openness individuals might experience fewer barriers to or fear from a close-contact experience with patients affected by mental illness and might exhibit lower levels of prejudice related to mental illness. Considering that prejudice can be reliably related to some personality traits more than others (1618) and, therefore, it might be tendentially less present in those projecting themselves in a psychiatric career, related research has highlighted how stigmatizing attitudes about persons affected by mental illness may influence medical students’ view and choice of psychiatry as a medical specialty (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of the same tendency, high-openness individuals might experience fewer barriers to or fear from a close-contact experience with patients affected by mental illness and might exhibit lower levels of prejudice related to mental illness. Considering that prejudice can be reliably related to some personality traits more than others (1618) and, therefore, it might be tendentially less present in those projecting themselves in a psychiatric career, related research has highlighted how stigmatizing attitudes about persons affected by mental illness may influence medical students’ view and choice of psychiatry as a medical specialty (19).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that, within the medical profession, psychiatry is viewed as lacking scientific basis and as not being medical enough (2, 26, 27). Increasingly healthcare professionals, including doctors and medical students, are identified as significant sources of prejudice and discrimination (19, 2833). Medical students in particular likely view people with mental illnesses as unpredictable, dangerous, and untreatable, while they express distancing attitudes toward them (3436).…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, research about stigma in health students in Portugal has demonstrated the need for stigma reduction intervention in this group of students (Querido, Tomás, & Carvalho, 2016). Anti-stigma specific education (Gil, 2015;Telles-Correia, Marques, Gramaça, & Sampaio, 2015), clerkship (Petkari, Masedo Gutierrez, Xavier, & Moreno Kustner, 2018)…”
Section: Introductionmentioning
confidence: 99%
“…However, the ongoing global recruitment crisis in psychiatry (Brown andRyland, 2019, Choudry andFarooq, 2017;Crabb et al 2017;Maidment et al, 2003;Rajagopal et al, 2004), means that adequate workforce planning and retention is essential to ensure that evidence based care and treatment can be effectively delivered. Early exposure to psychiatry through experiential learning in medical school is shown to increase positive attitudes towards and interest in psychiatry as a career choice (Economou et al, 2017;Warnke et al, 2017;Petkari et al, 2018). To achieve this, however, psychiatry may require a higher profile in medical curricula, perhaps even placed as an equal partner alongside medicine and surgery.…”
Section: Introductionmentioning
confidence: 99%